Job Satisfaction Analysis Using Minnesota Satisfaction Questionnaire (MSQ) In the Public Sector - Maulida Nailissaadah; Suharnomo Suharnomo (Budapest International Research and Critics University, 2022)
Face revolution industry 4.0 and competition between company that very competitive, company need own source power which qualified. Source power man rated important because considered capable synergize with source power which other in effort reach objective organization. Satisfaction work is Thing important which expected by para employee moment they work in something company. For create satisfaction work, no easy because there is many the factor that affect it. Minnesota Satisfaction Questionnaire (MSQ) is which used in study this. Study this researching the difference between Gen X and Gen Y for differentiate level satisfaction work them. Study this use method analysis quantitative. In study this got results that no there is difference significant level satisfaction work employee generations X and Y. But on the indicator variety, ability utilization, working condition, security and creativity. there is difference level satisfaction.